Thinking skills course and student's academic self-efficacy - AlShaibani, Yania A; Daoud, Jamal Ibrahim (2011)
The purpose of this study is to examine the impact of thinking skills courses on undergraduate students' academic self-efficacy. The study also examines the differences between students who have been involved in thinking skills courses and those who have yet to enroll in thinking skills course. The study also investigates the relationship between gender and students' academic self-efficacy. The study is limited to students of the Faculty of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University, Malaysia who have been enrolled in RKGS 2010 thinking skills course. Data was collected from 260 (male-female) undergraduate students. The College Academic Self-Efficacy Scale (CASES) instrument was used for data collection. The study used SPSS version 17 for the purpose of data analysis. The internal consistency reliability test was used to check the reliability of data measuring students' academic self-efficacy. The findings of this study support the hypothesis that thinking skills has direct relationship with academic self-efficacy. Thinking skills have influenced students' academic self-efficacy. In other words, the results support the effect of thinking skills courses on students' academic self-efficacy. Therefore, this study recommends that the duration of teaching thinking skills courses be lengthened as it has tremendous impact on students' academic self-efficacy.